FOOD GRADE NANOSTRUCTURES OF PUMPKIN LEAVES PROTEIN/PULLULAN BLEND AS A POTENTIAL CARRIER FOR COBALAMIN - Salević-Jelić, Ana; Knežević-Jugović, Zorica; Bugarski, Branko; Marković, Smilja; Nedović, Viktor; Đorđević, Verica; Balanč, Bojana (Food and Feed Research, 2024)
Nowadays, nanostructures made of biopolymers, such as proteins and polysaccharides, have gathered the growing attention of food scientists. In this study, pumpkin leaves from field crop side streams were processed to produce the protein isolate. The leaf protein isolate was investigated given the ability to encapsulate cobalamin (vitamin B12) in a blend with pullulan by electrospinning method. The starting blend solutions were characterized regarding the key factors that influence the formation of the fibers: viscosity, charge density carried by the jet, and surface tension. The results showed that the addition of the protein isolate (1% w/v) increased the conductivity of the pullulan solution (5% w/v), from 0.163 mS/cm to 1.420 mS/cm and the viscosity from 1.74±0.07 to 8.34±0.09 mPas. Cobalamin (at a concentration of 0.3 mg/mL) decreased the conductivity (to 0.978 mS/cm) and slightly increased the surface tension and viscosity of the final solution. SEM micrographs showed the formation of beads-on-fiber structures after the electro-hydrodynamic processing of the solutions. The protein caused the reduction of the beads compared to the beads obtained from neat pullulan (176.68 nm vs. 357.52 nm), while the mean fiber diameter was not affected ( 22.5 nm). The combination of biopolymer pullulan and protein-rich pumpkin leaf extract has shown the properties of a potential carrier for the model vitamin